MEMBANGUN KOMUNITAS KRISTIANI DAYAK MERATUS KEUSKUPAN BANJARMASIN KALIMANTAN SELATAN DALAM TERANG AD GENTES ARTIKEL 15 - Tjuandi, Yohanes (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
The church is the fruit of Christ's mission. The success of preaching theGospel begins with debriefing and then ends with mission, but continuedformation must be continued. Missionary work that is 'ad intra' (coaching)and 'ad extra' (planting) and is a picture of a Christian Community.Banjarmasin diocese with the MDD “Meratus Dayak Development” programevaluates three stations in the interior of South Kalimantan that are stillinfantile because they tend to be 'pastor-centric' and depend on volunteers.The existence and essence of Ad Gentes article 15, which describes theformation of the Christian congregation, is a weapon for the reconstruction ofthe Meratus Dayak Christian Community (MDCC). The STAR movementprogram or The Stasi Revitalization Movement is expected to furtherstrengthen the faith of Dayak Meratus Catholics to become more independentand resilient in carrying out the five tasks of the Church based on the 'spirit'of the CBE (Community Based Ecclesiastical) and Contextual Catechesis.